2021
DOI: 10.1130/b35905.1
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircons from Late Paleozoic Ice Age sequences in Victoria Land (Antarctica): New constraints on the glaciation of southern Gondwana

Abstract: The Lower Permian tillites of the Beacon Supergroup, cropping out in Victoria Land (Antarctica), record climatic history during one of the Earth’s coldest periods: the Late Paleozoic Ice Age. Reconstruction of ice-extent and paleo-flow directions, as well as geochronological and petrographic data, are poorly constrained in this sector of Gondwana. Here, we provide the first detrital zircon U-Pb age analyses of both the Metschel Tillite in southern Victoria Land and some tillites correlatable with the Lanterman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Based on flow directions, the Wynyard Fm is proposed to have been deposited by an ice mass centered in North Victoria Land (NVL), Antarctica, with contributions from ice masses located adjacent to the Dundas Trough (Fig. 1;Hand, 1993;Henry et al, 2012;Veevers, 2006;Zurli et al, 2022). Prior provenance work has demonstrated that most Wynyard Fm clast lithologies are attributable to pre-Permian source rocks in western Tasmania (Banks, 1981;Hand, 1993), and not NVL sources.…”
Section: Geologic Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on flow directions, the Wynyard Fm is proposed to have been deposited by an ice mass centered in North Victoria Land (NVL), Antarctica, with contributions from ice masses located adjacent to the Dundas Trough (Fig. 1;Hand, 1993;Henry et al, 2012;Veevers, 2006;Zurli et al, 2022). Prior provenance work has demonstrated that most Wynyard Fm clast lithologies are attributable to pre-Permian source rocks in western Tasmania (Banks, 1981;Hand, 1993), and not NVL sources.…”
Section: Geologic Contextmentioning
confidence: 99%
“…flowed generally from south to north through the Dundas Trough (Fig. 1A; Hand, 1993), 2. had a warm (temperate) thermal regime (Henry et al, 2012;Ives, 2021;Powell, 1990), and 3. was part of, possibly an outlet glacier or ice stream of, a larger ice sheet that was centered over North Victoria Land (e.g., Ives, 2021;Veevers, 2006;Zurli et al, 2022).…”
Section: Implications For the "Wynyard Glacier"mentioning
confidence: 99%
See 1 more Smart Citation